Condition of cleanliness of surfaces close to patients in an intensive care unit - Ferreira, Adriano Menis (2012)
ABSTRACT - Surface cleaning is a well-known control procedure against the dissemination of microorganisms in the hospital environment. This prospective study, carried out in an intensive care unit over the course of 14 days, describes the cleaning/disinfection conditions of four surfaces near patients. In total, 100 assessments of the surfaces were carried out after they were cleaned. Three methods were used to evaluate cleanliness: a visual inspection, an adenosine triphosphate (ATP) bioluminescence assay and testing for the presence of Staphylococcus aureus and meticillin-resistant Staphylococcus aureus/MRSA. Respectively, 20%, 80% and 16% of the assessments by the visual method, ATP and the presence of Staphylococcus aureus/MRSA failed. There were statistically significant differences (p<0.05) between the rates of failure of the cleaning using the ATP method, compared to the visual and microbiological methods. The visual inspection was not a reliable measure to evaluate surface cleanliness. The results demonstrated that the adopted cleaning routine should be reconsidered.